Comparative FISH mapping of 45S and 5S rDNA in the genus Gambierdiscus advances understanding of the cytogenetic diversity and mitosis of dinoflagellates. Issue 3 (3rd July 2022) - Cuadrado, Angeles; Sixto, Marta; Figueroa, Rosa I.; Bravo, Isabel; de Bustos, Alfredo
ABSTRACT: Dinoflagellates are protists with exceptionally large genomes and chromosomes that lack nucleosomes. To date, information on their genome organization is scarce. Studies investigating the distribution of ribosomal RNA genes (rDNA) in plants and animals by fluorescence in situ hybridization (FISH) have provided important information to elucidate the genome organization and evolution of many species. In the present study, FISH was used to analyse the chromosomal organization of 45S and 5S rDNA and the extent of rDNA variation among five species of Gambierdiscus ( G. australes, G. excentricus, G. silvae, G. carolinianus and G. caribaeus ). The results, the intensity and location of the FISH signals, are summarized as follows: (1) All Gambierdiscus species have extremely high copy number of 45S rDNA repeat units arranged in a large nucleolus situated in the concave region of the typical interphasic bean-shaped nucleus. In addition, outside the large nucleolus, G. silvae and G. carolinianus have minor clusters of 45S rDNA repeats. (2) Many copies of 5S rDNA organized in one or a few clusters, depending on the species, are physically separated from the 45S rDNA but located close, peripherally, to the nucleolus. This nuclear organization is preserved during cell division. (3) Gambierdiscus australes was the species with the lowest 5S rDNA FISH signals clustered into a single site. In contrast, one major and several minor 5S rDNA clusters of FISH signals were observed in G. excentricus . We find that the species analysed can be differentiated by their species-specific FISH rDNA phenotypes demonstrating the usefulness of FISH in comparative cytogenomic studies of Gambierdiscus . In addition, using G. australes as a model, we demonstrate the usefulness of 45S and 5S rDNA as chromosomal markers to study dinomitosis, the atypical nuclear division that solely occurs in the class Dinophyceae.